For the Handicapped, Rights But No Welcome - Will, George F. (The Hastings Center report, 1986)
The multiplication of rights— legally enforceable claims on the attention, actions, and resources of others—can carry us only so far. Improvements for the handicapped depend primarily on improving the attitudes of the nonhandicapped majority through appeals to conscience and good will.